2019
DOI: 10.2174/1570162x17666190327153038
|View full text |Cite
|
Sign up to set email alerts
|

The Pattern of Non-AIDS-defining Cancers in the HIV Population: Epidemiology, Risk Factors and Prognosis. A Review

Abstract: : The advent of highly active antiretroviral therapy (HAART) has significantly reduced the incidence of AIDS events, including AIDS-defining malignancies. Nevertheless, several cohort studies conducted in the post-HAART period have reported an increasing risk of non-AIDS-defining cancers (NADC). : Overall, the potential mechanisms leading to an increased risk of developing NADCs probably involve multiple known and unknown factors. In addition to ageing, chronic inflammation and ongoing immune system dysregul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 116 publications
2
42
0
Order By: Relevance
“…Interestingly, some studies demonstrated that, in HIV patients treated with HAART [ 220 , 221 , 222 , 223 ], the incidence rate of some cancers is, in fact, lower. Corroborating these findings, results from other studies reported associations of a potential anti-neoplastic impact of HAART [ 224 , 225 , 226 , 227 ]. It has been shown that ritonavir induces apoptosis of lymphoblastic tumour cells including lymphoma, myeloid leukaemia, fibrosarcoma, mastocytoma, and Kaposi’s sarcoma [ 228 , 229 , 230 , 231 ].…”
Section: Drug Repurposing For Ovarian Cancer Therapysupporting
confidence: 71%
“…Interestingly, some studies demonstrated that, in HIV patients treated with HAART [ 220 , 221 , 222 , 223 ], the incidence rate of some cancers is, in fact, lower. Corroborating these findings, results from other studies reported associations of a potential anti-neoplastic impact of HAART [ 224 , 225 , 226 , 227 ]. It has been shown that ritonavir induces apoptosis of lymphoblastic tumour cells including lymphoma, myeloid leukaemia, fibrosarcoma, mastocytoma, and Kaposi’s sarcoma [ 228 , 229 , 230 , 231 ].…”
Section: Drug Repurposing For Ovarian Cancer Therapysupporting
confidence: 71%
“…Severe alterations in the immune system result in higher prevalence of clinically relevant HPV infections. In fact, co-infection with HIV has been shown to impair cell-mediated immune control of HPV infections (62). Host genetics and other influences on host immunity might also affect the immune response to HPV infection; weak associations of human leukocyte antigen DRB1 and DQB1 genes with risk of CIN3 have been described (63).…”
Section: Natural History Of Hpv Infection and Research In Lamentioning
confidence: 99%
“…Combination antiretroviral therapy (cART) has improved immune function and reduced the risk of developing AIDS in individuals with HIV-1 infection [1,2]. In line with the improved viral control achieved by cART, the risk of developing AIDS-defining cancers, such as Kaposi sarcoma (KS) and non-Hodgkin lymphoma (NHL), have declined significantly, whereas non-AIDS defining malignancies, such as plasmablastic lymphoma (PBL) and classical Hodgkin´s lymphoma (cHL), have remained stable or increased in incidence [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%